PNEUMATIC CONTROL SYSTEMS IN TECHNICAL AND INFORMATION TECHNOLOGY EDUCATION - ŚLEZIAK, Mariusz (Trends in education, 2015)
Teaching program introduces students of technical courses related to mechatronics. One of the first steps toward teaching students the Technical-Information Education is the design of pneumatic control systems.Graduate with access to modern industry at the time of education is valuable to employers because it reduces the costs associated with training and preparation for work in office.
Keywords: pneumatics; pneumatic controls; technical -information education; training.